Cytokeratin positivity in myxopapillary ependymoma - a potential diagnostic pitfall - Sur Monalisa; Hussein Sundus A (BMC, 2008)
Abstract Background Myxopapillary ependymomas (MPE) occur in the filum terminale of the spinal cord, but also present in extra-spinal locations such as subcutaneous tissue and brain. They are slow growing grade I gliomas. Areas of solid growth pattern with aggregates of cells with "epithelioid morphology" seen in MPE can mimic metastatic carcinoma. The presence of occasional cells with clear cytoplasm and morphology can resemble Chordoma. Diagnosis can be missed due to these morphological similarities, which could affect patient management and hence, long term survival. Case presentation We describe two cases of MPE with cytokeratin (AE1 AE3, CAM 5.2, Cytokeratin 7 and cytokeratin 20) expression. Conclusion MPE can be positive for Cytokeratins (CAM 5.2, AE1 AE3, CK7) and focally for EMA, which could be misdiagnosed as metastatic carcinoma. In cases demonstrating epithelioid and clear cell morphology, the diagnosis of MPE should be made in conjunction with histology, proper immunohistochemical profile which includes co-expression of GFAP, S-100 protein and epithelial markers, radiologic findings and site. It is important to be aware of the cytokeratin profile in MPE to avoid erroneous diagnosis with other tumour entities.